HURLER'S SYNDROME : EFFECT OF RETINOL (VITAMIN A ALCOHOL) ON CELLULAR MUCOPOLYSACCHARIDES IN CULTURED HUMAN SKIN FIBROBLASTS - Danes, B. Shannon (The Rockefeller University Press, 1966)
Skin fibroblasts from eight families with Hurler's syndrome (X-linked recessive and autosomal recessive) and normal individuals have been studied in cell culture. A good correlation between cellular metachromasia and the quantitative estimation of intracellular mucopolysaccharides was observed provided the culture conditions were standardized. In both forms of Hurler's syndrome intracellular mucopolysaccharide content could be used to distinguish the affected individual and the carrier from the normal subject, although the total mucopolysaccharide content of fibroblast cultures or the amount in the culture medium did not permit such a distinction. Retinol, in concentrations similar to those encountered in man in hyper-vitaminosis A, caused a reduction in total mucopolysaccharide content of fibroblast cultures from normal and affected individuals. Cultures from three patients with the X-linked recessive form of Hurler's syndrome showed a gradual but marked decrease in cellular metachromasia and approximately 60% decrease in mucopolysaccharide content. Synthesis of polysaccharides and sulfation appeared to be equally affected. On removal of retinol from the medium the content of intracellular mucopolysaccharides returned to pretreatment levels. The possible relevance of these findings to the treatment of Hurler's syndrome is discussed.